Does chronic raise of metal ion levels induce oxidative DNA damage and hypoxia‐like response in patients with metal‐on‐metal hip resurfacing?. Issue 2 (19th October 2015) - Savarino, Lucia; Fotia, Caterina; Roncuzzi, Laura; Greco, Michelina; Cadossi, Matteo; Baldini, Nicola; Giannini, Sandro
ABSTRACT: Metal‐on‐metal hip resurfacing (MOM‐HR) represents a viable alternative to traditional arthroplasty. Nevertheless, in MOM coupling both metal nanoparticles and ions are released, whose toxicity remains a matter of concern. We investigated whether 'endogenous' chronic exposure to cobalt and chromium induced a state of oxidative stress, DNA damage and a hypoxia‐like response in patients with well‐functioning MOM‐HR. Twenty‐two patients with unilateral MOM‐HR were recruited at long‐term. Twenty‐one osteoarthritic subjects were enrolled for comparison. Serum ion levels were measured and correlated with 8‐hydroxydeoxyguanosine and circulating‐free‐DNA, as markers of oxidative DNA damage. Moreover, the hypoxia‐inducible factor‐1α, marker of hypoxic state, was evaluated. Ion concentrations were found to be 5‐to‐15 times higher in MOM‐HR patients than in presurgery subjects ( p  < 0.001); circulating‐free‐DNA, 8‐hydroxydeoxyguanosine, and hypoxia‐inducible factor‐1α levels were not significantly different between groups and did not correlate with ion levels. Analyzing the results according to gender, MOM‐HR males had higher 8‐hydroxydeoxyguanosine levels ( p  = 0.01) compared with MOM‐HR females. Similarly, circulating‐free‐DNA values were higher in males than females, even if this difference did not reach statistical significance. This research is the first that attempted to investigate the long‐term effects of ion dissemination in subjects with well‐fixed MOM implants. A significant correlation between biomarkers increase and ion levels was not demonstrated. Nevertheless, both circulating‐free‐DNA and 8‐hydroxydeoxyguanosine showed a tendency to increase in MOM‐HR males. Further studies with a larger sample size should be performed to detect the clinical relevance of biomarkers increase especially in younger subjects, where a chronic moderately elevated exposure has to be faced. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 460–466, 2017.